Rare Case Studies of Bilateral and Symmetric Sacroiliac Disease - Stephen Soloway; Alyxandra M. Soloway; Tyler G. Chin; Timothy Lieske (Case Reports in Rheumatology)
Introduction. Inflammatory sacroiliitis is common in rheumatology practice. Spondyloarthritis is often underdiagnosed due to the lack of proper evaluation of the sacroiliac joints (SIJs), clinically and radiographically. If SIJ is inflamed or arthritic, the arthritic said patient typically has spondyloarthritis, in the absence of infections or crystal arthritis. Sacroiliitis, in particular, when diagnosed between 12 and 45 years of age, is indicative of spondyloarthritis. People are often misdiagnosed and mislabeled as fibromyalgia because their serologies are negative. Our goal is to point out the importance of proper evaluation, diagnosis, and importance of inflammatory SIJ disease and conditions that involve SIJ inflammation. Cases. We present three rare conditions presenting with bilateral and symmetric SIJ disease, none of which is ankylosing spondylitis, Crohn’s colitis, ulcerative colitis, psoriatic arthritis, and reactive arthritis (Reiter syndrome); there are reports of concurrent SIJ disease in rheumatoid arthritis and SLE. Conclusion. The authors believe that SIJ disease is overlooked, is underdiagnosed, and can lead to incorrect treatment. We suggest a greater focus on SIJ imaging in the diagnosis and treatment of unexplained illnesses associated with low back pain, morning stiffness, or unexplained buttock pain. Providers should review their own SIJ films. The meaning of SIJ widening, cortical irregularity, spurs, and the significance of the anterior inferior SI joints, bone marrow edema, and fusion (namely, the natural history of sacroiliac pathophysiology).